THE COURSE OF HEPATITIS C INFECTION AND RESPONSE TO ANTI-VIRAL THERAPY IN PATIENTS WITH THALASSEMIA MAJOR AND HEPATITIS C INFECTION: A LONGITUDINAL, PROSPECTIVE STUDY. - Sanaa Kamal; Sara Abdelhakam, Dr.; Dahlia Ghoraba; Mohamad Amer Mohsen; Ahmed Abdelsalam; Huda Hassan; Leila Nabeigh (Mediterranean Journal of Hematology and Infectious Diseases)
Background/Aims: The course of hepatitis C infection (HCV) in patients with thalassemia has not been adequately studied and management has not been optimized. The current prospective longitudinal study assessed the clinical course, outcome, progression and management of recently acquired HCV in patients with transfusion dependent thalassemia major versus acute HCV without thalassemia. Methods: A well-characterized cohort of patients with thalassemia and recent HCV infection or recent HCV without thalassemia were enrolled and prospectively followed. The blood transfusion needs and chelating agents were determined. Liver functions tests, HCV-RNA, iron and ferritin levels were measured. Patients with chronic HCV evolution received treatment for HCV. The fibrosis progression rate was determined in chronic HCV patients with or without thalassemia by paired liver biopsies or serial transient elastography (TE), or serum markers of liver fibrosis. Liver iron content (LIC) was assessed by R2 MRI.